CONTROL INTERNO Y SU INCIDENCIA EN LA GESTION DE LAS CUENTAS POR COBRAR DE LA COOPERATIVA DE TRANSPORTE “TAXIS ALIANZA”, AÑO 2023 - Cedeño Espinoza, Sara Mishelle (2025)
This research was conducted with the main objective of evaluating the internal control and its impact on the accounts receivable management of the “Taxis Alianza” Transportation Cooperative, during the period 2023. A descriptive and evaluative type of research, deductive, analytical and synthesis methodology was applied and the practices and strategies applied in the administration were identified. Surveys, interviews with the population involved (manager, administrative personnel) and a COSO I evaluation were used. The results revealed weaknesses in internal control, especially in risk identification and mitigation, process monitoring, and the application of economic sanctions. The lack of a formal code of ethics, inadequate staff training and the absence of risk assessments affected management efficiency. In addition, there was a reliance on manual methods of account recovery, which hindered systematic and timely follow-up. In financial terms, accounts receivable turnover was low, reflecting a prolonged collection cycle and difficulties in recovering receivables. Delinquency and the lack of adequate allowance for doubtful accounts compromised the cooperative's liquidity. For this reason, it was recommended that risk identification and control be strengthened, collection processes be automated and economic sanctions be established to improve efficiency in the recovery of accounts. These strategies will optimize financial management and guarantee the stability of the cooperative.